Preparation of Flood Disaster Contingency Documents in Pesisir Selatan Regency, West Sumatra, as Part of Disaster Risk Reduction (Mitigation) : Penyusunan Dokumen Kontingensi Bencana Banjir di Kabupaten Pesisir Selatan, Sumatera Barat dalam Rangka Pengurangan Risiko (Mitigasi) - Fauzan, Fauzan; Rinaldi Ekaputra; Abdul Hakam; Bambang Istijono (Universitas Lancang Kuning, 2025)
The development of a contingency document is a process of identifying and planning for future scenarios that are likely to occur but not certain. Following the flood disaster in Pesisir Selatan Regency in 2024, a community service activity under the community partnership program to assist village development (PKM-MNM) was carried out. This activity involved preparing a flood disaster contingency document as a guideline for managing emergency flood disaster response in Pesisir Selatan Regency to ensure that emergency response can be managed quickly and effectively. The focus area of the program included disaster mitigation efforts (before, during, and after the disaster). Additionally, the guideline serves to coordinate human resources and facilities during emergency flood responses. The preparation of this contingency document involved several stages, including aligning perceptions through a Forum Group Discussion (FGD), conducting survey data collection for the contingency document, verifying data on-site, socializing the preparation of the contingency document, drafting risk assessment and disaster response plans, and reporting and evaluating activities. The resulting flood disaster contingency document encompasses flood characteristics and scenarios, identifying flood-prone areas, intensity, duration, and impacts. It includes assumed impacts such as infrastructure damage, evacuations, and service disruptions, preparedness measures outlining instructions and coordination among parties for effective response, and action plans covering operational strategies, evacuation, and the provision of emergency aid. This program successfully enhanced community involvement, particularly through Disaster Preparedness Groups (KSB), in disaster mitigation and preparedness. The outcomes of this PKM-MNM activity are expected to transform partner regions into disaster-resilient areas fostered by universities and co-funded by local governments, CSR initiatives, and other sponsors. The contingency document produced from this activity is also anticipated to serve as a reference for further studies on disaster risk management in other regions with similar geographical characteristics.